General Election and the Study of the Future - Tomy Michael (Warmadewa Press, 2018)
Indonesia's position in electoral development is getting better because of the legislation. It is different when a strong bargaining position is artificial. In this case, the state becomes strong because of its own efforts such as having sophisticated technology programs, producing sophisticated weapons, or having world-class athletes. The problem is when the candidate listed in the empty ballot has been elected by the community but the chosen one does not win, then such election is actually not of the will of the community. This study uses normative legal study design which means that it is normative juridical legal research. The approaches used in legal research are statute approach, case approach, and conceptual approach. Future elections will no longer change when there is no legal clarity in Indonesia if the robot is included in it. The election aimed at robots for is not being a contradiction but is a way out to produce elections that are truly fair. When we choose robots in the elections, artificial intelligence holds norms in society. Artificial intelligence will become a habit in Indonesia, turning to jus cogens because its main nature is indirect force.